Pacific walrus diet across 4000 years of changing sea ice conditions. (July 2022) - Clark, Casey T.; Horstmann, Lara; de Vernal, Anne; Jensen, Anne M.; Misarti, Nicole
Abstract: Declining sea ice is expected to change the Arctic's physical and biological systems in ways that are difficult to predict. This study used stable isotope compositions (δ 13 C and δ 15 N) of archaeological, historic, and modern Pacific walrus ( Odobenus rosmarus divergens ) bone collagen to investigate the impacts of changing sea ice conditions on walrus diet during the last ~4000 yr. An index of past sea ice conditions was generated using dinocyst-based reconstructions from three locations in the northeastern Chukchi Sea. Archaeological walrus samples were assigned to intervals of high and low sea ice, and δ 13 C and δ 15 N were compared across ice states. Mean δ 13 C and δ 15 N values were similar for archaeological walruses from intervals of high and low sea ice; however, variability among walruses was greater during low-ice intervals, possibly indicating decreased availability of preferred prey. Overall, sea ice conditions were not a primary driver of changes in walrus diet. The diet of modern walruses was not consistent with archaeological low sea ice intervals. Rather, the low average trophic position of modern walruses (primarily driven by males), with little variability among individuals, suggests that trophic changes to this Arctic ecosystem are still underway or are unprecedented in the last ~4000 yr.